3,3 '-Diindolylmethane Improves Intestinal Permeability Dysfunction in Cultured Human Intestinal Cells and the Model Animal Caenorhabditis elegans - Kim, Joo Yeon; Tram Anh Ngoc Le; Lee, So Young; Song, Dae-Geun; Hong, Sung-Chul; Cha, Kwang Hyun; Lee, Jae Wook; Pan, Cheol-Ho; Kang, Kyungsu (AMER CHEMICAL SOC, 2019)
3,3'-Diindolylmethane (DIM), a digestive metabolite originating from cruciferous vegetables, has dietary potential for the treatment of various human intestinal diseases. Although intestinal permeability dysfunction is closely related to the initiation and progression of human intestinal inflammatory diseases (IBDs), the effect of DIM on intestinal permeability is unclear. We evaluated the effect of DIM on the intestinal permeability of human intestinal cell monolayers and the animal model Caenorhabditis elegans, which were treated with IL-1 beta and Pseudomonas aeruginosa, respectively, to mimic IBD conditions. DIM substantially restored the intestinal permeability of differentiated Caco-2 cells by enhancing the expression of tight junction proteins (including occludin and ZO-1). Compared to the IL-1 beta single treatment (551.0 +/- 49.0 Omega.cm(2)), DIM (10 mu M) significantly increased the transepithelial electrical resistance (TEER) of Caco-2 cell monolayers (919.0 +/- 66.4 Omega.m(2), p < 0.001). DIM also ameliorated the impaired intestinal permeability and extended the lifespan of C. elegans fed P. aeruginosa. The mean lifespan of DIM-treated worms (10.8 +/- 1.3 days) was higher than that of control-treated worms (9.7 +/- 1.1 days, p < 0.01). Thus, DIM is a potential nutraceutical candidate for the treatment of leaky gut syndrome by improving intestinal permeability.
Keywords: ARYL-HYDROCARBON RECEPTOR; PSEUDOMONAS-AERUGINOSA; TOPOISOMERASE INHIBITOR; ACTIVATION; BARRIER; COLITIS; INDOLE-3-CARBINOL; INFLAMMATION; SUPPRESSES; EXPRESSION